Pengaruh Senioritas, Work Performance, Dan Kompetensi Terhadap Employee Promotion PT. Roki Indonesia - Putri, Chairunissa Permana; Gopar, Ida Abdul (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Every organization and company certainly strives to improve the performance of employees who work for the company, with the hope that all organizational goals can be achieved as well as possible. One of the company's efforts to improve employee performance is by implementing an employee promotion program implemented at PT Roki Indonesia. This research is quantitative, with a population of 50 respondents, using purposive sampling method. the data collection methods used in this study are observation, questionnaire data and literature study. The data analysis technique uses multiple linear regression tests, hypothesis testing using the t test and the coefficient of determination test. The conclusion of this study is that the seniority variable and the work performance variable partially have no effect on employee promotion, while the competency variable partially affects employee promotion at PT Roki Indonesia.